1952
DOI: 10.2307/1538405
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Acrosome. I. Reaction to Egg-Water and Other Stimuli

Abstract: 1. Spermatozoa of two sea urchin species were fixed with formalin in sea water, egg-water and sea water of pH 9.2, and observations of fixed specimens made with phase contrast and electron microscopes were compared with phase contrast observation in the living state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0
1

Year Published

1961
1961
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(67 citation statements)
references
References 8 publications
1
65
0
1
Order By: Relevance
“…The outer acrosomal membrane and the overlying plasma membrane fuse and vesiculate when spermatozoa are presented with physiological inducers from the female gamete, its vicinity, or to appropriate pharmacological stimuli. This unique, tightly regulated, irreversible, single exocytotic process releases the acrosomal contents, modifies membrane components, and exposes the inner acrosomal membrane to the extracellular medium (130,131,571). Sperm egg-coat penetration and fusion with the eggs' plasma membrane require the release and exposure of cell components resulting from this exocytotic process, named the acrosome reaction (AR).…”
Section: A Generalitiesmentioning
confidence: 99%
“…The outer acrosomal membrane and the overlying plasma membrane fuse and vesiculate when spermatozoa are presented with physiological inducers from the female gamete, its vicinity, or to appropriate pharmacological stimuli. This unique, tightly regulated, irreversible, single exocytotic process releases the acrosomal contents, modifies membrane components, and exposes the inner acrosomal membrane to the extracellular medium (130,131,571). Sperm egg-coat penetration and fusion with the eggs' plasma membrane require the release and exposure of cell components resulting from this exocytotic process, named the acrosome reaction (AR).…”
Section: A Generalitiesmentioning
confidence: 99%
“…A factor associated with eggs (jelly coat) normally causes induction of the acrosome reaction in sea urchin spermatozoa (Popa, 1927;Dan, 1952Dan, , 1956. A protease similar to or identical with acrosin is released in response to these jelly coat factors and, based on protease inhibitor studies, Levine & Walsh (1979) have suggested that activation of this protease is required for successful completion of an acrosome reaction.…”
Section: Introductionmentioning
confidence: 99%
“…There were a very few reports using one or the other of these methods in the study of fertilization during the 1940s (Harvey and Anderson, 1943;Austin and Smiles, 1948), but in no case were these approaches used in concert. In describing the acrosome reaction, Dan published whole-mount, shadow-casting electron micrographs; however, she emphasized the essential role of phase contrast microscopy in that it permitted her to compare those results in glutaraldehyde-fi xed specimens with living sperm -to wit, all "the points have been checked in the living condition" (Dan, 1952). As such, Dan's work depended on the application to fertilization of new methodologies.…”
mentioning
confidence: 99%